EFFECT OF RESTING TIME ON PERIPHERAL BLOOD MONONUCLEAR CELL YIELDS - Narayani, Inna; Niruri, Rasmaya; Astawa, Nyoman Mantik (International Journal of Biosciences and Biotechnology, 2016)
Cryopreservation of PBMC (peripheral blood mononuclear cells) was done to preserve and analyze the number of PBMC derived from blood samples which come in at different time. The batch analysis wasperformed at the same time in order to reduce variations in results. The analysis on the cells numbers carried out after 1, 3, 6, 12, and 24 hours. Heparinized whole blood was collected from healthy subject by venipuncture, and stored at room temperature. Blood is processed by centrifugation in Ficoll density gradient following the established method of Balai Besar Veteriner Denpasar. Buffy coat layer was collected and washed twice with HBSS (Hank's balanced salt solution) and was counted in Turk’s solution. The cells were then dissolved in 1 ml of cold freezing medium containing 10% DMSO and 50% FBS (fetal bovine serum) and stored overnight at -80°C before storage in liquid nitrogen vessel for few weeks. The samples rapidly thawed in a water bath at 37°C and washed twice with PBS (phosphate buffered saline). The cells were stored in 4°C PBS and counted in Turk’s solution after 1, 3, 6, 12, and 24 hours. The results obtained were varied with a declining trend.
Keywords: buffy coat; cell count; PBMC; resting time